Dinamika Pelaksanaan Kebijakan Program Pelayanan Penyandang Masalah Kesejahteraan Sosial Anak Jalanan - Rachmawati, Vita; Faedlulloh, Dodi (Journal of Political Issues, 2021)
This research is motivated by the relatively high number of people with social welfare problems for street children in North Jakarta compared to other cities in the DKI Jakarta Province. Therefore, serious efforts from the government are needed to overcome this problem. This study discusses the dynamics of the implementation of the policy on the service program for people with social welfare problems for street children in North Jakarta.. This study uses a qualitative method. To select informants, researchers used purposive sampling. To measure the validity of the study, the researcher used source triangulation by comparing data from observations and interviews, conditions with people's perspectives, and interviews with document content. The results showed that the communication process in the implementation of handling street children has not been implemented properly. This occurs because there are conditions in the delivery of information that are still ineffective. Furthermore, resources related to staff, information, authority, and facilities also each have shortcomings so that they lack effectiveness in terms of policy resources. In the context of disposition, it shows that policy implementers have not yet optimal responses in implementing policies on handling street children in North Jakarta. Meanwhile, from the bureaucratic structure, the implementing institution has its own SOP. The implementation of policies on handling street children in North Jakarta has not experienced fragmentation.